Combining Quantitative and Qualitative Methods for Program Monitoring and Evaluation: Why Are Mixed-Method Designs Best? - Adato, Michelle (World Bank, Washington, DC, 2012)
Despite significant methodological advances, much program evaluation and monitoring data are of limited utility because of an over-reliance on quantitative methods alone. While surveys provide generalizable findings on what outcomes or impacts have or have not occurred, qualitative methods are better able to identify the underlying explanations for these outcomes and impacts, and therefore enable more effective responses. Qualitative methods also inform survey design, identify social and institutional drivers and impacts that are hard to quantify, uncover unanticipated issues, and trace impact pathways. When used together, quantitative and qualitative approaches provide more coherent, reliable, and useful conclusions than do each on their own. This note identifies key elements of good mixed-method design and provides examples of these principles applied in several countries.